2017
DOI: 10.23938/assn.0046
|View full text |Cite
|
Sign up to set email alerts
|

Does Omega-3 supplementation after the age of 65 influence cognitive function? Results of a systematic review

Abstract: Fundamento. El porcentaje de población de edad avanzada aumenta progresivamente y con ello las enfermedades asociadas a la edad como el deterioro cognitivo (DC) y la demencia. Distintos estudios sugieren que dietas ricas en ácidos grasos poliinsaturados omega-3 (AGPI w-3) pueden reducir el riesgo de DC y demencia. El objetivo fue evaluar si existe evidencia sobre la relación entre la suplementación con AGPI w-3 en pacientes ≥ 65 años y la función cognitiva. Material y métodos.Se recuperaron 582 artículos relac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It is very difficult to evaluate the association between each individual nutrient and the risk of dementia, because everybody eats complex combinations of nutrients that might have synergic effects through non well known mechanisms [ 65 ]. A recent systematic review that analyzed the association between supplements and dementia found that studies conducted with multinutrients supplementation had better results over dementia [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is very difficult to evaluate the association between each individual nutrient and the risk of dementia, because everybody eats complex combinations of nutrients that might have synergic effects through non well known mechanisms [ 65 ]. A recent systematic review that analyzed the association between supplements and dementia found that studies conducted with multinutrients supplementation had better results over dementia [ 66 ].…”
Section: Discussionmentioning
confidence: 99%